Perdagangan Bebas Produk Farmasi dan Alat Kesehatan serta Kesiapan Memenuhi Persyaratan Cetak Biru Masyarakat Ekonomi ASEAN - Prayitno, Lukman; Herman, Max Joseph (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2020)
The implementation of the ASEAN Economic Community (AEC) as an Indonesian Government’s strategic step has an impact on economic globalization. The study on pharmaceutical products and medical devices free trade was done using qualitative and quantitative methods. The data were collected from a round table discussion about